2021
DOI: 10.1007/s40262-020-00956-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Pharmacokinetics and Exposure–Response Relationship of Dapagliflozin in Patients without Diabetes and with Chronic Kidney Disease

Abstract: Background and Objective Dapagliflozin, a sodium-glucose co-transporter inhibitor, was originally developed as an oral glucose-lowering drug for the treatment of type 2 diabetes mellitus. Emerging data suggest that cardiovascular and kidney benefits extend to patients without diabetes. Limited pharmacological data are, however, available in patients without diabetes. We aimed to characterise the pharmacokinetic profile of dapagliflozin in patients with chronic kidney disease without type 2 diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
1
8
1
Order By: Relevance
“…Reducing both renal and non–renal elimination of key TGT components likely changes the in vivo exposure of these components. The plasma exposure of five key TGT components (TPL, WFG, WFT, WFD, and WFR) and the tissue contents of six key TGT components (TPL, WA, WFG, WFT, WFD, and WFR) in the heart, liver, spleen, lung, kidney, and brain increased significantly after single–dose TGT administration in NS rats ( Figures 5 , 6 and Table 1 ), consistent with previous reports that the plasma exposure of certain drugs increased when kidney function declined ( Albrecht et al, 2017 ; van der Aart-van der Beek et al, 2021 ). Furthermore, the cumulative exposure of four key TGT components (TPL, WFG, WFT, and WFD) in the kidney and liver also increased after multi–dose TGT administration in NS rats, particularly advanced–stage NS rats ( Figure 7 ).…”
Section: Discussionsupporting
confidence: 90%
“…Reducing both renal and non–renal elimination of key TGT components likely changes the in vivo exposure of these components. The plasma exposure of five key TGT components (TPL, WFG, WFT, WFD, and WFR) and the tissue contents of six key TGT components (TPL, WA, WFG, WFT, WFD, and WFR) in the heart, liver, spleen, lung, kidney, and brain increased significantly after single–dose TGT administration in NS rats ( Figures 5 , 6 and Table 1 ), consistent with previous reports that the plasma exposure of certain drugs increased when kidney function declined ( Albrecht et al, 2017 ; van der Aart-van der Beek et al, 2021 ). Furthermore, the cumulative exposure of four key TGT components (TPL, WFG, WFT, and WFD) in the kidney and liver also increased after multi–dose TGT administration in NS rats, particularly advanced–stage NS rats ( Figure 7 ).…”
Section: Discussionsupporting
confidence: 90%
“…Results of a mixed-effects model studying PK and exposure-response of dapagliflozin in patients with CKD reported that every 100 ng • h/mL rise in dapagliflozin exposure was associated with a decrease in eGFR (β = −0.5 mL/min/1.73 m 2 ; P < .01), thereby supporting our findings. 3 The popPK model characterizing dapagliflozin PK in patients with HFrEF also found that the systemic exposure was 1.5-and 1.8-fold higher in patients with reduced kidney function (eGFR of 45-59 and 30-44 mL/min/1.73 m 2 , respectively) than in those with a normal eGFR (≥90 mL/min/1.73 m 2 ). 21 The 10-mg once-daily dose of dapagliflozin has been deemed safe and is recommended for patients with CKD, T2DM, and HFrEF.…”
Section: Discussionmentioning
confidence: 95%
“…Dapagliflozin is a highly potent, selective, and reversible sodium-glucose cotransporter 2 inhibitor, developed as an oral antihyperglycemic drug to lower plasma glucose and glycated hemoglobin by blocking renal glucose reabsorption in the proximal tubule, thereby improving urinary glucose excretion. [1][2][3] Dapagliflozin, taken once daily (up to 10 mg), has been approved by the US Food and Drug Administration (FDA), by the European Medicines Agency, and in Japan, as well as numerous countries worldwide, for the treatment of type 2 diabetes mellitus (T2DM) in adults, and it is also approved for the treatment of type 1 diabetes mellitus (T1DM) in Japan. [4][5][6][7] However, the benefits of dapagliflozin extend beyond achieving glycemic control to reducing the risk of renal, cardiovascular, and mortality end points in patients with and without T2DM, as reported by the Dapagliflozin and Prevention of Adverse Outcomes in Chronic Kidney Disease (DAPA-CKD) and Dapagliflozin and Prevention of Adverse Outcomes in Heart Failure (DAPA-HF) clinical trials, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying mechanisms of this individual variation in response to SGLT2 inhibition are incompletely understood. Systemic exposure to several SGLT2 inhibitors is variable between patients and related to responses in metabolic variables including glycemic control, body weight, and systolic blood pressure [ 17 , 18 , 19 , 20 ]. Less is known about the association between exposure to SGLT2 inhibition and responses in kidney variables including kidney hemodynamic changes.…”
Section: Introductionmentioning
confidence: 99%